2015
DOI: 10.4028/www.scientific.net/amm.772.435
|View full text |Cite
|
Sign up to set email alerts
|

Modal Analysis of Hummingbird Inspired MAV Flapping Wings

Abstract: Natural flyers are the best source of inspiration for making successful MAVs. Hummingbirds are known for their excellent flight characteristics such as long duration hovering, backward flying, high agility, etc. Giant hummingbird is chosen as the bio-inspiration for designing the wing. Wings are required to be light, strong, and fatigue resistant to be used for MAV applications. Carbon nanotubes (CNTs)/Polypropylene (PP) composite is chosen as the wing membrane material whereas carbon fiber (CF)/epoxy (E) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Another type of bird wing inspired by nature, known as the hummingbird, has also made progress in flapping wing UAVs due to its flapping mechanism and excellent characteristics of high agility and maneuverability, backward motion, long duration hovering, and being able to rotate their wings 180°. Kumar et al [ 47 ] used ANSYS Fluent to perform fluid-structure interaction, where CFD simulation is conducted to study the aerodynamic performance of the wing of a giant hummingbird and compared it with the experimental study. It can be found that the wing was excited at 14 Hz, with negative drag indicated as positive thrust with high Cl .…”
Section: Research On Biomimetics Related To Cfd Applicationsmentioning
confidence: 99%
“…Another type of bird wing inspired by nature, known as the hummingbird, has also made progress in flapping wing UAVs due to its flapping mechanism and excellent characteristics of high agility and maneuverability, backward motion, long duration hovering, and being able to rotate their wings 180°. Kumar et al [ 47 ] used ANSYS Fluent to perform fluid-structure interaction, where CFD simulation is conducted to study the aerodynamic performance of the wing of a giant hummingbird and compared it with the experimental study. It can be found that the wing was excited at 14 Hz, with negative drag indicated as positive thrust with high Cl .…”
Section: Research On Biomimetics Related To Cfd Applicationsmentioning
confidence: 99%
“…Various angles of attack, wingtip trace patterns, wing areas and complex adjustments to feather orientation can be combined to enable advanced flight capabilities 11 – 13 . In the design of MAV wings, the relationships between wing length, wing area and body weight should be considered 14 . To design an MAV that can generate the maximum thrust and lift with the minimum body weight, it is necessary to assess the dependence of the lift and thrust on the wing shape and area 15 .…”
Section: Introductionmentioning
confidence: 99%